2014
DOI: 10.4049/jimmunol.1302100
|View full text |Cite
|
Sign up to set email alerts
|

Effector-Memory T Cells Develop in Islets and Report Islet Pathology in Type 1 Diabetes

Abstract: CD8+ T cells are critical in human type 1 diabetes and in the NOD mouse. In this study, we elucidated the natural history of islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP)-specific CD8+ T cells in NOD diabetes using MHC-tetramer technology. IGRP206–214-specific T cells in the peripheral lymphoid tissue increased with age, and their numbers correlated with insulitis progression. IGRP206–214-specific T cells in the peripheral lymphoid tissue expressed markers of chronic Ag stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 33 publications
7
51
0
Order By: Relevance
“…The latter point has been debated: using double-retrogenic mice, in which specificity is controlled, Lennon et al (11) showed that only antigen-specific cells accumulate in the insulitis after transfer into NOD.scid mice, and only T cells specific for β-cell antigens localized to islets in the first hours after transfer (12,13) in other studies. However, antigen-specific cells identified by tetramer staining are only modestly enriched in the pancreas relative to irrelevant lymphoid organs, and there is still ample participation by other cells (14,15). Polyclonal populations, unlikely to be antigen specific, accompanied cells from specific clones injected into NOD mice (16).…”
mentioning
confidence: 99%
“…The latter point has been debated: using double-retrogenic mice, in which specificity is controlled, Lennon et al (11) showed that only antigen-specific cells accumulate in the insulitis after transfer into NOD.scid mice, and only T cells specific for β-cell antigens localized to islets in the first hours after transfer (12,13) in other studies. However, antigen-specific cells identified by tetramer staining are only modestly enriched in the pancreas relative to irrelevant lymphoid organs, and there is still ample participation by other cells (14,15). Polyclonal populations, unlikely to be antigen specific, accompanied cells from specific clones injected into NOD mice (16).…”
mentioning
confidence: 99%
“…In the NOD model, there was an increase of islet-specific glucose-6-phosphatase catalytic subunit related protein (IGRP)-specific CD8 + T EM cells in the peripheral lymphoid tissue (spleen and peripheral lymph nodes) after 10 weeks of age, which correlated with severity of insulitis in these mice (48). In our CTLA4RNAi/B6.H2 g7 model of juvenile-onset T1D that harbors a natural polyclonal T-cell repertoire as in the NOD model, we did not detect substantial impact of CD8 + memory T cells on the early onset of autoimmune diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…These populations increased in frequency as the mice aged and were able to migrate into the islets. IGRP specific CD8 þ T cells could mediate target cell lysis and developed a memory phenotype with age [57,61]. Insulin specific CD4 þ T cells from NOD mice were able to produce IFNg upon stimulation [58].…”
Section: Phenotyping Islet-specific T Cells In Nod Mice Reveals Multimentioning
confidence: 98%